El Ejército Nacional de Colombia como agente de desarrollo territorial: una revisión al programa Fe en Colombia en el departamento del Caquetá (2020)
The Department of Caquetá has been one of the territories most affected by the Colombian armed conflict, a fact that should be directly proportional to the institutional effort for social recovery and the development of communities during the post-conflict period. In this vein, the National Army, through its Fe in Colombia (Faith in Colombia) Program, carries out actions with a view to strengthening civil-military relations and influencing the development of the Department by undertaking of new functions that respond to a changing context and an expanded concept of security. This text examines the role of this institution in generating development in Caquetá from the Fe en Colombia initiative.